A Prospective Study for the Assessment of Frailty in Elderly Chronic Kidney Disease Patients - Narinder Pal Singh; Mohd Qasim Khan; Pankaj Nand Choudhary; Anish Kumar Gupta; Shaurya Kaul (Indian Journal of Medical Specialities)
Background: Frailty is a common clinical syndrome in the elderly that may be associated with increased risk of health complications and decreased physical functioning. Early screening of individuals who are at high risk of frailty is required to allow timely intervention for the prevention and reversal of frailty. There is a paucity of information on frailty among the Indian elderly population and especially among the elderly chronic kidney disease (CKD) population. Hence, the aim of the present study was to find out the occurrence of frailty in elderly patients with CKD. Methods: The present prospective cross-sectional study was conducted from an outpatient clinic of a tertiary care hospital. We enrolled 200 participants aged 60 years or above, dividing them into two groups as case (included those with CKD stage 3 and above who were not on dialysis with or without any coexisting comorbidities) and control groups (included those non-CKD patients with or without any coexisting comorbidities). Exclusion criteria were patients with prior history of stroke with neurological complications, dementia or cognitive deficit, severe Parkinson's disease, and nonambulatory. Assessment of frailty was done using the short physical performance battery test (SPPBT) and handgrip strength (HGS). Assessment of HGS was done using a JAMAR hand dynamometer. The data were analyzed using SPSS V 20.0. Results: Majority of the participants were male in the case group (58%), while they were almost equal in the control group (51%). Most of the participants belonged to the age groups of 60–70 years with a mean age of 68.8 ± 5.90 years and 67.99 ± 5.93 years in case and control groups, respectively. In the case group, more than half of the patients had CKD stage 4 (57%), followed by CKD stage 5 (36%). There was no significant difference in diabetes mellitus (P = 0.41), hypertension (P = 0.63), malignancy (P = 1.0), CLD (P = 0.097), and thyroid disorder (P = 0.85) among the groups. Using SPPBT, frailty was found to be significantly higher in CKD patients in comparison to control (78% vs. 62%, P = 0.014). Using the HGS criteria, frailty was detected almost similar in both the groups (CKD vs. non-CKD; 77% vs. 78%, P = 0.866). Frailty was found to be high (78.5%) in CKD patients who had estimated glomerular filtration rate of <30 ml/min. Moreover, frailty was significantly higher in those with diabetes with CKD than diabetic alone (P = 0.009). Conclusion: Frailty was found to be high in elderly patients with CKD as compared to the non-CKD population. This indicates a need for continuous assessment of frailty and timely tailored intervention for prevention and reversal of frailty in the elderly CKD population.